Protocol of Kupffer phase whole liver scan for metastases: A single-center prospective study - Wu, Qiong; Liu, Yilun; Sun, Di; Wang, Yan; Wei, Xiaoer; Li, Jing; Liu, Beibei; Wang, Shuhao; Zhou, Yan; Hu, Haiyan; Zhang, Rui; Jiao, Qiong; et al. (Frontiers in Medicine, 2022)
Introduction: As the presence of hepatic metastases is very important to cancer patients' clinical stage which would directly affect the selection and application of anti-cancer treatments. Although conventional ultrasound is commonly performed as a screening tool, most of the examinations have relatively poor sensitivity and specificity for detecting liver metastases. Contrast-enhanced ultrasound (CEUS) with Sonazoid has been reported to have the advantage of the diagnosis and therapeutic support of focal hepatic lesions and its specific Kupffer phase whole liver scan (KPWLS) is believed to be sensitive to detect liver metastases. And the purpose of this study is to determine the number, size, location and diagnosis of metastatic lesions, and to compare the results with conventional ultrasound and contrast-enhanced computed tomography (CECT), thus to clarify the application value, indications of Sonazoid-CEUS in screening liver metastasis. Methods and Analysis: Kupffer phase whole liver scan for metastases (KPWLSM) is a self-control, blind map-reading, single-center, prospective superiority trial. Approved by the institutional review committee, the study period is planned to be from 1 January 2022 to 31 December 2025. Our study will include 330 patients with history of malignant tumors that cling to metastasize to liver. All patients will undergo the examinations of conventional ultrasound, Sonazoid-CEUS, and contrast-enhanced magnetic resonance imaging (CEMRI), and 65 of them should have additional CECT scans. The primary endpoint is the comparative analysis of the numbers of detected liver metastatic lesions among Sonazoid-CEUS, conventional ultrasound and CECT in screening liver metastases. Subjective conditions of patient after injection of Sonazoid will be followed up 3 and 30 days after KPWLSM, and any short-term and long-term adverse events are to be recorded with telephone interviews. Ethics and Dissemination: This study has been granted by the Ethics Committee of Shanghai Jiao Tong University Affiliated Sixth People’s Hospital (Approval No: 2021-197). When the KPWLSM is completed, we will publish it in an appropriate journal to promote further widespread use. Registration: Trial Registration Number and Date of Registration: Chinese Clinical Trial Registry, ChiCTR2100054385, December 16, 2021.